Opinions, Arguments, and the Persuasive (pithanon) in Epictetus - Dinucci, Aldo; Rudolph, Kelli (Revista Archai, 2026)
Epictetus follows Stoic orthodoxy - and Zeno’s own definition - by emphasizing the importance of logic in detecting sophisms. He goes so far as to assert that it is a virtue that subsumes four others: carefulness, caution, irrefutability and seriousness. In this paper, we argue that Epictetus’ interest in the testing of presentations extends also to premises and arguments. We demonstrate how Epictetus, following Chrysippus, creates a systematic approach to understanding sophisms/arguments. The philosopher must understand the consequences of what has been granted, offer valid demonstrations, follow the demonstrations of his interlocutors, and ultimately be able to detect sophisms. These sophisms, as well as the premises and arguments connected with them, are often characterized by Epictetus as pithanon. We argue that what he means by this is that the sophisms and their components are deceptive, often deliberately so. To make such a judgement, however, the philosopher must master Stoic dialectics and the study of sophisms.